Host HDAC4 regulates the antiviral response by inhibiting the phosphorylation of IRF3. (25th May 2018) - Yang, Qi; Tang, Jielin; Pei, Rongjuan; Gao, XiaoXiao; Guo, Jing; Xu, Chonghui; Wang, Yun; Wang, Qian; Wu, Chunchen; Zhou, Yuan; Hu, Xue; Zhao, He; et al.
Abstract: Class II HDACs, such as HDAC4, are critical regulators of the immune response in various immune cells; however, its role in innate immunity remains largely unknown. Here, we report that the overexpression of HDAC4 suppresses the production of type I interferons triggered by pattern-recognition receptors (PRRs). HDAC4 repressed the translocation of transcription factor IRF3 to the nucleus, thereby decreasing IRF3-mediated IFN-β expression. In particular, we also determined that HDAC4 can be phosphorylated and simultaneously block the phosphorylation of IRF3 at Ser386 and Ser396 by TBK1 and IKKε, respectively, by interacting with the kinase domain of TBK1 and IKKε. Furthermore, IFN-β may stimulate the expression of HDAC4. Our findings suggest that HDAC4 acts as a regulator of PRR signaling and is a novel mechanism of negative feedback regulation for preventing an over-reactive innate immune response.